An important innovation in the area of оld high german syntax and its genesis. Observations based on the old high german Tatian - Dentschewa, Emilia (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
The basic features of the syntactic system of German can already be found in Germanic. Two essential factors determine the further development of syntax - the effect of the Germanic final sound laws as a result of the establishment of the strongly dynamic accent on the first syllable of the word (initial accent) and the increasingly complicated linguistic communication in the course of social development. On the one hand, the changes in the wording led to a violation of the functional-grammatical clarity of many nominal and verbal forms, which led to the emergence of morphological substitute forms for expressing the syntactic connections in the sentence – articles for nouns, subject pronouns for verbs, analytical paraphrases of cases, analytical descriptions of verbal functional units. The need to grasp complex facts (also through language contact) required, on the other hand, a stronger development of parataxis and hypotaxis, as well as a stronger consolidation of word order. In the context of this article, attention is focused on the state of development of the nominal-verbal sentence with regard to the explicit subject indexing in the Old High German translation of Tatian from the first half of the 9th century. The observations arose in connection with the work on the creation of the “Linguistic Key to Old High German Tatian” (based on the edition by Eduard Sievers) which was published in December 2023 by the University Press „St. Kliment Ohridski“ Sofia. It is emphasized that the extremely frequent autonomous use of the subject pronoun in Tahd can obviously be seen as the result of a rule for explicitly identifying the pronominal subject that is already well established. In modern German, this rule will dictate mandatory pronominal subject indexing. Finally, it is pointed out that the development of the analytical type of personal indication in Old High German must be viewed as a late consequence of the imposition of a dynamic word-initial stress in Germanic.